Perbedaan Epistemologi Bayani, Irfani dan Burhani dalam Pemikiran Islam - Ulliyah, Anggun Khafidhotul; Aulia, Eva Nur; Ikhsan, Muhammad Azka Waradana; Ramadhani, Rifki Fajar; Nasikhin; Junaedi, Mahfud; Aarde, Timothy Van (MAN 1 Kota Kediri, 2024)
Epistemology is the theory of knowledge in the context of Islamic philosophy, which includes three main approaches: Bayani, Irfani, and Burhani. The Bayani approach centers on the sacred text, while Irfani is concerned with direct experience of spiritual reality. On the other hand, the Burhani approach is based on logic. This research aims to analyze the differences in bayani, irfani and burhani epistemology. By using the literature research method, this study shows that there are differences in 1.) Bayani epistemology 2.) Irfani epistemology 3.) Burhani epistemology. In this study, the analysis of Bayani, Irfani, and Burhani epistemology shows significant differences. The Bayani approach tends to produce dogmatic and intolerant religious views, while the Burhani approach offers an open and philosophical framework. The Irfani 2 approach, on the other hand, explores the dimensions of spiritual experience in depth. The results of this study have a positive impact on the development of Islamic science, strengthening the argument that Western philosophers' thoughts can synergize with Islamic philosophy. By understanding the differences and relevance of each approach, space can be opened for dialogue between intellectual traditions, supporting conflict resolution and promoting peace with a more contextual and scientific approach. Keywords: Epistemology, Bayani, Irfani, Burhani.